2020
DOI: 10.1007/s40119-020-00183-6
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Outcomes of Patients with Acute Decompensated Heart Failure and Cirrhosis: An Analysis of the National Inpatient Sample

Abstract: Introduction Heart failure increases morbidity and mortality in patients admitted for cirrhosis. Our objective was to determine if patients with acute decompensated heart failure (ADHF) and cirrhosis would have increased mortality, hospital length of stay (LOS), and total hospital charges compared to patients with only ADHF. There is also a paucity of data regarding the influence of gender, race, ethnicity, insurance, and cirrhosis-related complications on mortality, hospital length of stay, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The presence of underlying cirrhosis increases mortality risk in patients with HF. A recent analysis by Khalid et al [7] showed an in-patient mortality rate of 3.4% among HF hospitalized patients with cirrhosis. Cirrhosis leads to a chronic hyperdynamic circulatory state coupled with low systemic vascular resistance, and provides a backdrop for independent cardiomyopathy from the risk factors for the etiology of cirrhosis in itself (such as NASH/amyloid/hemochromatosis) [8].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of underlying cirrhosis increases mortality risk in patients with HF. A recent analysis by Khalid et al [7] showed an in-patient mortality rate of 3.4% among HF hospitalized patients with cirrhosis. Cirrhosis leads to a chronic hyperdynamic circulatory state coupled with low systemic vascular resistance, and provides a backdrop for independent cardiomyopathy from the risk factors for the etiology of cirrhosis in itself (such as NASH/amyloid/hemochromatosis) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Yazdanyar et al (2021) [19] and Khalid et al (2020) [20] which investigated the outcomes of hospitalized patients with HF and LC showed a similar 3.4 % in-hospital mortality rate in this population. Further, according to Ge et al (2021) [21] , the cumulative incidence of death at 30 days is 12.5 % among those patients with LC and HF with concurrent COVID-19 infection.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, previous studies suggested that COVID-19 infection increases the risk for the development of acute renal failure leading to circulatory volume overload which subsequently worsens cardiac dysfunction among those patients with pre-existing HF [17] , [18] . Although previous studies have shown that there is increased risk for morbidity and mortality among hospitalized LC with concurrent HF [19] , [20] , there is still paucity of data regarding the incremental risk of COVID-19 in this population. With this, we aim to investigate the in-hospital outcomes among hospitalized LC patients with comorbid HF and concurrent COVID-19 infection by utilizing a large nationwide database.…”
Section: Introductionmentioning
confidence: 97%
“…It is a difficult disease to understand and it is associated with a mortality at 5 years of 51% [ 9 ]. However, there is no current consensus on survival or prognostic factors for portopulmonary hypertension due to a scarcity of studies as well as a lack of data secondary to a small number of patients enrolled in clinical trials, a situation similar to that for patients with pulmonary hypertension and cirrhosis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cirrhosis, alone or in combination with pulmonary hypertension, is known to increase total hospital charges, but this disease decreases mortality and hospital LOS independently of other risk factors, likely due to improvements in management and the rise of palliative care [ 10 ]. However, this is not the same for patients with cirrhosis-related complications, as can be seen in our study as well.…”
Section: Discussionmentioning
confidence: 99%